Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper provides an overview of the exchange rate and trade dynamics in Indonesia. Using data on monthly export and import price and volume at the sectoral level, the paper estimates pass-through effects of exchange rate changes to trade price and volume. Results indicate adjustment frictions that depend on the source of the exchange rate fluctuation and the degree of integration in global value chains. Overall, combining price and volume effects, we find that 10 percent depreciation in the exchange rate is associated with a rise in the goods net-exports of up to 1.6 percent of GDP. Results indicate that there is considerable asymmetry and sectoral heterogeneity in the pass-throughs of exchange rate on import and export prices. Import prices adjust well to exchange rate fluctuations with the effects being stronger for appreciation episodes. The price sensitivity of export prices to exchange rate shocks is generally lower than of imports and concentrated over shorter horizons and during episodes of depreciation. The price and quantity results imply that exchange rate changes can have significant effects on the current account, by affecting movements in net-exports of goods.